Clinical Features of Peritonsillar Abscess in Children - Hsiang-Ju Hsiao; Yhu-Chering Huang; Shao-Hsuan Hsia; Chang-Teng Wu; Jainn-Jim Lin (Pediatrics and Neonatology)
Peritonsillar abscess is an acute infection located between the capsule of the palatine tonsil and the superior constrictor muscle of the pharynx. The reports regarding pediatric cases have been scanty. Methods: A retrospective study was conducted to investigate the patients less than 18 years of age hospitalized at a medical center with a final diagnosis of peritonsillar abscess from January 1999 through December 2009. Only those who were confirmed by the drainage of pus from the peritonsillar spaces or confirmed by a computed tomography (CT) scan were enrolled. Results: In total, 56 children, 31 male and 25 female, were included. The mean age was 12.9 ± 4.6 years, ranging from 9 months to 17.9 years. Nineteen (34%) were less than 12 years of age. All 37 children ≧12 years of age complained of sore throat, but only 68% of children less than 12 years of age complained of sore throat. Thirty-one patients (55%) with a characteristic presentation of fever and sore throat plus an asymmetric swollen/bulging tonsil with or without uvular deviation suggestive of the diagnosis received surgical drainage at emergency department immediately, and 87% of them were older than 12 years of age. Twenty-five (45%) children needed a CT scan to confirm the diagnosis. The most common empirical antibiotics were penicillin-containing regimens. The predominant organisms identified were Streptococcus species. Eight children were treated successfully with antibiotics alone. No case was fatal. Conclusion: Two-thirds of the children with peritonsillar abscess were ≥12 years of age. Not every patient <12 years of age had a characteristic presentation, and a CT scan was usually needed to confirm the diagnosis.